Go Green: Memberdayakan Masyarakat Rawa Buntu Serpong Dengan Menanam Sayuran dan Rempah-rempah - Sudarmanto, Eko; Aulia, Triana Zuhrotun; Siregar, Indra Gunawan; Erdawati, Lena; Isrok Isrok; Saputra, M Wahid; Purnamasari, Yuana Fasya (Lembaga Pengembangan Kinerja Dosen, 2024)
The